OXIDATION ISOTHERMAL AND MICROSTRUCTURE STUDY OF ALCOCRCUFENI HIGH ENTROPI ALLOY AT 900, 1000, AND 1100? - Fariq Marcopolo, Juan
Fe, Ni, and Co base superalloys has been utilized for high temperature operation such as rocket’s nozzle, nuclear reactor system, jet-airplane turbine blade, airplane gas turbine engine, power plant turbine engine, power plant boiler engine, gas turbine, and motor engine exhaust facilities, although utilizing at higher temperature will be hampered by the solvus and the melting temperature of the alloys. As an alternative, researchers introduced a new class of alloys that contain five or more elements known as “high entropy alloys”. These materials have low cost for manufacturing but can perform a better performance when operated in higher temperature. High entropy alloy of AlCoCrCuFeNi equimol were tested in some isothermal oxidation resistance test with intention to learn the microstructure, the evolution of the microstructure of the alloys, the mechanism of the oxidation process, the kinetics of the oxidation process, and the influence of oxidation test to the hardness properties of the alloys with variation of time 2 hours, 16 hours, and 40 hours along with the variation of temperature 900?, 1000? and 1100?. Microstructure and the evolution observed by optical microscope, characterized by X-Ray Diffraction (XRD) and Scanning Electron Microscope – Energy Dispersive X-Ray Spectroscopy (SEM-EDS). The kinetics of the oxidation process observed by the difference of the mass that processed to gain similar equation with the results test. The influence of oxidation test to hardness properties observed by Hardness Vickers Testing Machine. The data from the test will be processed and plot to gain hardness trend in varions of time and temperatures. In general, the microstructure of the AlCoCrCuFeNi alloys have a decompositional spinodal-like morphology. The main phases are AlNi-rich, Co-Cr-Fe solid solution and Cu segregation along with the Al-rich as secondary phase. The evolution of microstructure is Cu segregations is fining and spreading in the matrix.The oxide that showed up such as Al2O3, Cr2O3, FeO, NiO, CoO, CuO, spinel NiO-Al2O3 dan spinel NiCr2O4. The kinetic oxidation process follows parabolic law which means the kinetics of the process controlled by the diffusion of the species that pass by the oxides layer. The influence of oxidation test to hardness property generally will be decreased along with increase of time and temperature.